A national study of practice patterns in UK renal units in the use of dialysis and conservative kidney management to treat people aged 75 years and over with chronic kidney failure - Paul Roderick; Hugh Rayner; Sarah Tonkin-Crine; Ikumi Okamoto; Caroline Eyles; Geraldine Leydon; Miriam Santer; Jonathan Klein; Guiqing Lily Yao; Fliss Murtagh; Ken Farrington; Fergus Caskey; et al. (National Institute for Health Research, 2015)
Background: Conservative kidney management (CKM) is recognised as an alternative to dialysis for a significant number of older adults with multimorbid stage 5 chronic kidney disease (CKD5). However, little is known about the way CKM is delivered or how it is perceived. Aim: To determine the practice patterns for the CKM of older patients with CKD5, to inform service development and future research. Objectives: (1) To describe the differences between renal units in the extent and nature of CKM, (2) to explore how decisions are made about treatment options for older patients with CKD5, (3) to explore clinicians' willingness to randomise patients with CKD5 to CKM versus dialysis, (4) to describe the interface between renal units and primary care in managing CKD5 and (5) to identify the resources involved and potential costs of CKM. Methods: Mixed-methods study. Interviews with 42 patients aged > 75 years with CKD5 and 60 renal unit staff in a purposive sample of nine UK renal units. Interviews informed the design of a survey to assess CKM practice, sent to all 71 UK units. Nineteen general practitioners (GPs) were interviewed concerning the referral of CKD patients to secondary care. We sought laboratory data on new CKD5 patients aged > 75 years to link with the nine renal units' records to assess referral patterns. Results: Sixty-seven of 71 renal units completed the survey. Although terminology varied, there was general acceptance of the role of CKM. Only 52% of units were able to quantify the number of CKM patients. A wide range reflected varied interpretation of the designation 'CKM' by both staff and patients. It is used to characterise a future treatment option as well as non-dialysis care for end-stage kidney failure (i.e. a disease state equivalent to being on dialysis). The number of patients in the latter group on CKM was relatively small (median 8, interquartile range 4.5-22). Patients' expectations of CKM and dialysis were strongly influenced by renal staff. In a minority of units, CKM was not discussed. When discussed, often only limited information about illness progression was provided. Staff wanted more research into the relative benefits of CKM versus dialysis. There was almost universal support for an observational methodology and a quarter would definitely be willing to participate in a randomised clinical trial, indicating that clinicians placed value on high-quality evidence to inform decision-making. Linked data indicated that most CKD5 patients were known to renal units. GPs expressed a need for guidance on when to refer older multimorbid patients with CKD5 to nephrology care. There was large variation in the scale and model of CKM delivery. In most, the CKM service was integrated within the service for all non-renal replacement therapy CKD5 patients. A few units provided dedicated CKM clinics and some had dedicated, modest funding for CKM. Conclusions: Conservative kidney management is accepted across UK renal units but there is much variation in the way it is described and delivered. For best practice, and for CKM to be developed and systematised across all renal units in the UK, we recommend (1) a standard definition and terminology for CKM, (2) research to measure the relative benefits of CKM and dialysis and (3) development of evidence-based staff training and patient education interventions. Funding: The National Institute for Health Research Health Services and Delivery Research programme.